CALCULUS AND ITS APLLICATIONS - Bittinger Marvin L. (Pearson, 2004)
FUNCTIONS, GRAPHS AND MODELS DIFFERENTIATION APPLICATIONS OF DIFFERENTIATION EXPONENTIAL AND LOGARITHMIC FUNCTIONS INTEGRATION APPLICATIONS OF INTEGRATION FUNCTIONS OF SEVERAL VARIABLES
FUNCTIONS, GRAPHS AND MODELS DIFFERENTIATION APPLICATIONS OF DIFFERENTIATION EXPONENTIAL AND LOGARITHMIC FUNCTIONS INTEGRATION APPLICATIONS OF INTEGRATION FUNCTIONS OF SEVERAL VARIABLES